SYNTHESIS AND CHARACTERIZATION OF POLYANILINE AS ACTIVE MATERIAL OF PLASTIC SOLAR CELLS - Wibowo (NIM 205 05 011), Arie
ABSTRACT: Energy shortage and global warming urge a tremendous research in the development of photovoltaic cells as one of renewable and environmental friendly energy. Besides researching to improve silicon-based solar cell, scientist was also devoted to the development of Plastic Solar Cells (PSC) because the PSCs offer low cost production, solution processing for large coating area, a very high speed of processing, flexible and light-weight. Hence many scientists believe that plastic solar cells are a promising low cost approach for solar energy conversion. However, plastic solar cells research still found obstacle at low efficiency and short life time. Short life time problem in PSCs is particularly susceptible to photodegradation of conductive polymer induced by oxygen and moisture. Polyaniline (PANI) is properly to overcome short life time problem in PSCs due to their stability with oxygen and moisture. To become active material in PSC, conductive polymers ought to have band gap less than 2.0 eV, it also have high hole mobility, the difference of donors Lowest Unoccupied Molecular Orbital (LUMO) to acceptors LUMO is more than 0.2 eV and absorption coefficient is as high as 10 5 cm -1. Because of that, in this work we synthesized and characterized PANI, both emeraldine base (EB) form and emeraldine salt (ES) form, to study PANI potency as active material in PSC. To ensure that EB and ES were synthesized, the functional groups of them were identified by Fourier Transform Infra Red (FTIR), the crystal structure of them was analyzed by X-Ray Diffraction (XRD) and the morphology and microstructure of them was characterized by Scanning Electron Microscopy (SEM). To know the maximum absorption wavelength and the optical band gap of materials, each sample was dissolved in N-methyl-2-pyrrolidone (NMP) and characterized by UV-VIS-NIR spectroscopy. For estimation of Highest Occupied Molecular Orbital (HOMO) / Lowest Unoccupied Molecular Orbital (LUMO) of EB, ES and Rhodamine B (used as acceptor electron), each sample was dissolved in NMP containing 0.1 M tetra-n-butyl ammonium perchlorate (TBAP) as supporting electrolyte and measured by Cyclic Voltammetry (CV) method. To calculate the hole mobility of materials, each sample pellet was characterized by Electrochemical Impedance Spectroscopy (EIS) method. From SEM image showed that both ES and EB are aggregated granular. From XRD pattern showed that ES more crystalline than EB. From UV-VIS-NIR measurement, EB has the maximum absorption at visible region with lambda = 630 nm, meanwhile ES has the maximum absorption at near infra red region with lambda = 1435 nm. This absorption shift showed that polaron was formed in ES sample with energy gap was smaller than EB. EB band gap (Eg opt) is 1.62 eV which can be estimated from UV-VIS-NIR data. ES band gap (Eg CV) is 1.02 eV which can be calculated from CV measurement. Both EBs and ESs relative position LUMO have difference more than 0.2 eV if coupled with Rhodamin B as acceptor electron. That means, charge transfer can be easily occurred from PANI to Rhodamin B. The hole mobility of EB is 17.04 cm 2 V -1 s -1 and the hole mobility of ES is 1.87 x 10 3 cm 2 V -1 s -1 which can be calculated from EIS measurement. Both ES and EB have potency as active material in PSC. Nevertheless ES has a larger potency as active material in PSC because a lower band gap and a higher hole mobility than EB.